2006
DOI: 10.1002/jcp.20813
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate regulates the anabolic activity of MC3T3‐E1 preosteoblast cells by induction of Runx2

Abstract: The transcription factor Runx2 can be controlled by a number of upstream regulators involved in intracellular signaling, including the activation ERK1/2 signaling by fibroblast growth factor-2 (FGF-2). FGFs interact with their cell surface receptors (FGFRs) through an obligate cross-binding interaction with heparan sulfate proteoglycan (HSPG) co-receptors; exogenous HS sugar chains have been shown to potently modulate changes in cell phenotype depending on the stage of tissue differentiation when the HS is har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 50 publications
(59 reference statements)
4
57
0
Order By: Relevance
“…Heparan sulfate proteoglycans, which are abundant on the cell surface and in the extracellular matrix, have emerged as major co-regulators controlling signaling pathways in osteogenic cells (44). Heparan sulfates increase the expression of bone-related biomarkers and maintain BMP signaling, and studies have suggested that this family of sugar-based compounds orchestrates the transition from proliferation to differentiation (3,33,44). Supporting this view, our study demonstrates that heparin strongly synergizes with Wnt3a and selectively stimulates the osteogenic but not mitogenic potential of Wnt3a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heparan sulfate proteoglycans, which are abundant on the cell surface and in the extracellular matrix, have emerged as major co-regulators controlling signaling pathways in osteogenic cells (44). Heparan sulfates increase the expression of bone-related biomarkers and maintain BMP signaling, and studies have suggested that this family of sugar-based compounds orchestrates the transition from proliferation to differentiation (3,33,44). Supporting this view, our study demonstrates that heparin strongly synergizes with Wnt3a and selectively stimulates the osteogenic but not mitogenic potential of Wnt3a.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the in vivo efficacy of bone anabolic factors (e.g. BMP2, 3 parathyroid hormone, and Wnts) is limited, and new molecular approaches to improve the effectiveness and selectivity of osteo-inductive extracellular ligands are desirable. Results from our group and others suggest that glycosaminoglycans (GAGs) and in particular heparan sulfate (HS) and heparin are potent co-stimulators of osteogenic signaling pathways, including BMP2-Smads and FGF-FGFR-MAPK (1-7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that some HSPGs, such as syndecans, expressed in the bone environment affect the osteoblast response to FGF2 during osteogenesis (Molteni et al 1999a). In vitro data indicate that both cell surface and secreted HSPGs can further amplify FGF2 signaling and osteoblast differentiation (Jackson et al 2007). Notably, the HSPG glypican-3 was found to be essential for Runx2 expression and subsequent osteoblast differentiation in vitro ).…”
Section: Fgf/fgfr Signaling In Osteoblastogenesismentioning
confidence: 99%
“…We have previously shown that HS helps control the osteogenic differentiation of preosteoblast MC3T3-E1 cells (12) and that exogenous application of such HS to cultures of rat bone marrow stem cells can stimulate their proliferation, which then leads to an increased expression of osteogenic markers and enhanced bone nodule formation (13). In recent years human mesenchymal stem cells (hMSCs) have been shown to be an important source of cells for tissue engineering applications.…”
mentioning
confidence: 99%